Plasma secretin and pancreatic bicarbonate response to exogenous secretin in man. Issue 3 (March 1977) - HACKI, W H; Bloom, S R; Mitznegg, P; Domschke, W; Domschke, S; Belohlavek, D; Demling, L; Wünsch, E
Abstract : The dose response of duodenal bicarbonate production during synthetic porcine secretin infusions was studied in six healthy volunteers and related to plasma secretin immunoreactivity. Secretin was infused in each individual at four different doses from 0-1 to 2-7 CU/kg/h, each infusion lasting for 60 minutes. Mean maximal bicarbonate secretion was 33 +/- 4 mEq/h. The secretin plasma level for half maximal bicarbonate response was estimated to be 22 pmol/l. As this level is reported to be achieved by intraduodenal acidification in man, it is concluded that secretin may well play a part in the control of duodenal pH.